ICT Skills and Competencies as Determinant to Reading Habit of LIS Undergraduates in Kwara State University - Sulaiman, Kabir Alabi; Akanbi, Mohammed Lawal; Bakare, Medinat Olayemi; Issa, Khairat Olosasa; Akolade, Nofisat Apelara; Agunbiade, Alimat Olajumoke; Muhammed, Ganiyat Omowumi; Arole, Mariam Adewumi (Jurusan Ilmu Perpustakaan dan Informasi Islam Universitas Islam Negerin Datokarama Palu, 2024)
This study investigates ICT skills and competencies as determinant to reading habit of LIS undergraduates in Kwara state university. The study adopted a Proportional stratified method, where the number of participants from each subgroup was determine by their number relatively to the entire population. The sample size of the study was 306 respondents which cut across all the levels of LIS students in Kwara State University. Data was collected using a questionnaire which was distributed to the 306 respondents in which all the copies of questionnaire were retrieved and used for the study. The data collected were analyzed using simple percentage and frequency count. The findings of the study were: word processing skills, spreadsheet skills and technical skills (maintenance) while on a contrary view minority disagreed with Software design skills and website design skills as the ICT skills that influence reading habit of LIS undergraduates. The study also found out that ICT is used for learning, mastering a range of assessment paradigins, and career development as ICT competencies that influence reading habit of LIS undergraduates. The study recommended that(i)Tertiary institutions offering LIS need to be provided with ICT facilities by the appropriate authorities to enhance the preparation of LIS students for the world of work. (ii)There should be a policy to ensure that all academic research study (project, thesis, dissertation, seminar, conference) are always presented in electronic form.